Evaluation of the potential effect of transgenic rice expressing Cry1Ab on the hematology and enzyme activity in organs of female Swiss rats. - Yang Wang; Baoyang Wei; Yixing Tian; Zhi Wang; Yun Tian; Shuduan Tan; Shengzhang Dong; Qisheng Song (PLoS ONE, 2013)
To assess the safety of transgenic rice expressing Cry1Ab protein to vertebrates, the effect of Cry1Ab rice on broad health indicators in blood and various organs of Swiss rats were analyzed. The 30 and 90 day safety studies of Cry1Ab rice on female Swiss rats revealed that Cry1Ab rice had no significant effect on the several elements of blood lymph including hemogram, calcium ion concentration and apoptosis rate of lymphocytes, indicating that Cry1Ab protein could not affect the blood lymph of Swiss rat. Similarly, Cry1Ab rice had no effect on enzyme activities in a variety of organs of Swiss rat. However, Cry1Ab rice did have significant effects on the blood biochemistry indexes including urea, triglyceride (TG), glutamic oxalacetic transaminase (AST) and alkaline phosphatase (ALP) after the rats were fed with Cry1Ab rice for 30 days, but not after 90 days, indicating that Cry1Ab protein may influence blood metabolism for a short duration. Quantitative real-time PCR (qPCR) analysis of the 6 genes encoding enzymes responsible for the major detoxification functions of liver revealed that Cry1Ab rice exerted no influences on the levels of these transcripts in liver of Swiss rat, indicating that significant differences registered in part of the blood biochemical parameters in the 30 day study might result from other untested organs or tissues in response to the stress of exogenous Cry1Ab protein. The results suggest that Cry1Ab protein has no significant long-term (90 day) effects on female Swiss rat.